Graphitization of banana peel – synergistic effect of Ca and other elements of the biomass on carbon structure transformation - Muhammad Jamshaid Shabbir; Barbara Liszka; Magdalena Szubka; Mirosława Pawlyta; Maciej Zubko; Jan Ilavsky; Karolina Jurkiewicz (Biomass and Bioenergy, 2026)

The rise of MXene: A new paradigm in 2D materials for energy storage devices - Muhammad Kaleem Shabbir; Javeed Akhtar; Fozia Arif; Haleema Asghar; Imamdin Chandio; Hafsa Khurshid; Khalid Hussain Thebo; Mohamed H. Helal (Journal of Environmental Chemical Engineering, 2026)

Propylparaben exposure induces hematobiochemical alterations, genotoxicity oxidative stress and apoptosis in Labeo rohita - Hasnain Akmal; Shabbir Ahmad; Muhammad Ahsan Riaz; Farhat Jabeen; Shahid Sherzada; Khurram Shahzad (Veterinary Research Communications, 2026)

Artificial Intelligence-assisted Discovery of Novel Bilastine and Bepotastine Analogs Against the Histamine H1 Receptor: Integrated Molecular Dynamics and MM/PBSA Evaluation - Muhammad Husnain; Shabbir Muhammad; Shamsa Bibi; Shafiq ur Rehman; Abdullah G. Al-Sehemi; Shimmaa Mansour Moustafa Mohamed; Saleh S. Alarfaji (Journal of Pharmaceutical Innovation, 2026)

Cytotoxic and computational profiling of 2-mercaptobenzimidazole Mannich derivatives: structure activity relationship and carbonic anhydrase binding assessment - Muhammad Naeem; Arooj Mohsin Alvi; Muhammad Mehmmod Moin Ul Haq; Najia Shabbir; Shumaila Mehdi; Areen Khalid; Saqib Khan; Hafiz Muhammad Ahmad; Najm Ul Hassan Khan; Muhammad Nouman Arif; Hafiz Aamir Ali Kharl (Inflammopharmacology, 2026)

Pathways to sustainable development: an examination of innovation and institutional quality’s role in green GDP Outcomes Using QCA - Muhammad Nadir Shabbir; Kainat Iftikhar; Mirza Muhammad Naseer (Environment, Development and Sustainability, 2026)

Advancements in Wheat Rust Resistance through Molecular and Field-Based Approaches - Muhammad Waheed Riaz; Dehua Wang; Shams ur Rehman; Yufeng Zhang; Faheem Tariq; Alam Sher; Shabbir Hussain; Muhammad Aamir Manzoor; Abdul Raziq; Zhiying Deng (Journal of Soil Science and Plant Nutrition, 2026)

Immunopharmacological and structural design of a polyprotein based multi epitope vaccine against Powassan virus - Aasia Kalsoom; Syed Hussain Abidi; Sohail Ameer Marwat; Ghulam Shabbir; Muhammad Naveed; Aiman Muhammad Ashraf Mughal; Muhammad Nouman Majeed; Shereen Magdy Korany; Basma Magdy Korany; Khaled Alzhrani; Tariq Aziz (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Syzygium cumini-mediated MnO2, Fe3O4 and Mn2FeO4 nanostructures for electrocatalytic water splitting - Fatima Ubaid; Riyadh H. Alshammari; Shabbir Hussain; Muhammad Arif; Muhammad Tariq; Khurram Shahzad Munawar; Asif Ali Tahir (Journal of Environmental Chemical Engineering, 2026)

Anti-inflammatory role of metal and metal oxide nanoparticles: a review of toxicity, green synthesis, and immunomodulatory mechanisms - Rimsha Ashraf; Shaukat Ali; Muhammad Summer; Saima Riaz; Amina Iqbal; Ramzana Bibi; Haiqa Shabbir (Inflammopharmacology, 2026)

Seroprevalence of crimean-congo hemorrhagic fever virus in large wildlife: a systematic review and meta-analysis - Aziz Ul-Rahman; Muhammad Abu Bakr Shabbir; Muhammad Zubair Shabbir; Muhammad Asif Raza (European Journal of Wildlife Research, 2026)

In situ biotransformation of synthetic glutamate to γ-amino butyric acid by an auxotrophic Lactococcus lactis in polysorbate-mediated thermoaerobic process - Siaknder Ali; Kinza Arif; Qaiser Farid Khan; Muhammad Usman Ahmad; Ifrah Shabbir; Iram Liaqat; Tawaf Ali Shah; Gehan M. Elossaily; Yousef A. Bin Jardan (Biodegradation, 2026)

CRISPR–anti-CRISPR dynamics: evolutionary, ecological and biotechnological perspectives - Javeria Idrees; Abdul Qadeer Shabbir; Iqbal Ahmad Alvi; Saba Sana; Shafiq ur Rehman; Muhammad Asif (Archives of Microbiology, 2026)

Review on flexible frameworks: Phosphazene functional polymers powering the future of membranes - Yasir Abbas; Muhammad Waqar Hameed; Zahid Ali; Ghulam Yasin; Kanwal Shabbir; Ijaz Hussain; Muhammad Ahsan Iqbal; Hafiz M. Adeel Sharif; Zhanpeng Wu; Nadeem Baig; Isam H. Aljundi; Niaz Ali Khan; et al. (Chemical Engineering Journal, 2026)

Evaluation of immunogenicity and protective efficacy of Salmonella Gallinarum knockout purB mutant strain in chicken - Muhammad Umer Farooq; Masham Mukhtar; Muhammad Suleman; Minahil Ashraf; Muhammad Abu Bakr Shabbir; Muhammad Hassan Mushtaq; Umar Bin Zahoor; Shakil Abbas; Aamir Ghafoor (Veterinary Research Communications, 2026)

Bacterial Metabolite-Derived NDM-1 Inhibitors: A Computational Strategy to Overcome β-Lactam Resistance - Bader S. Alotaibi; Farhat Shabbir; Muhammad Umer Khan; Iqra Ahmad; Hira Khalid; Shahid Aziz; Abid Ali; Sonia Younas; Hanna Dib; Khaled Fahmi Fawy; Umar Nishan; Mohibullah Shah (Probiotics and Antimicrobial Proteins, 2026)

Retraction Note: Does environmental sustainability affect the renewable energy consumption? Nexus among trade openness, CO2 emissions, income inequality, renewable energy, and economic growth in OECD countries - Iftikhar Muhammad; Rasim Ozcan; Vipin Jain; Paritosh Sharma; Malik Shahzad Shabbir (Environmental Science and Pollution Research, 2026)

Anti-arthritic and anti-inflammatory effects of BMZD-2CPE in a CFA and carrageenan-induced animal model - Samiullah Wazir; Farah Abid; Aisha Mobashar; Arham Shabbir; Muhammad Awais; Humaira Nadeem; Hafiz Aamir Ali Kharl; Esmael M. Alyami; Amir Bouallegue; Norah Hamdi; Mohammed Bourhia; Abdullah R. Alanzi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Adaptive Strategies of Carpet Grass to Drought: Insights from Physiological and Antioxidant Responses - Mohsin Nawaz; Samina Shabbir; Muhammad Mudassir Nazir; Muhammad Anas; Muhammed Farooq; Hu Xu; Wu Yang; Parvaiz Ahmad; Liao Li; Zhiyong Wang (Journal of Plant Growth Regulation, 2026)

Harnessing Paramecium primaurelia for polyhydroxyalkanoate production: optimization of carbon sources for sustainable bioplastic synthesis - Ayesha Arshad; Itrat Zahra; Awais Ibrahim; Usama Shabbir; Shahid Nawaz; Ayesha Liaqat; Roohi Ijaz; Tuba Arooj; Sammi Rasheed; Ayesha Ghauri; Bushra Muneer; Amor Hedfi; et al. (Biologia, 2026)

Exploring microbiological transformation of glutamate to γ-aminobutyric acid unleashed by a potential Lactobacillus spp. isolated from commercial cheese samples - Sikander Ali; Taha Shafi; Iram Liaqat; Muhammad Usman Ahmad; Ifrah Shabbir; Tariq Aziz; Maha Alharbi; Ashwag Shami; Fahad Al-Asmari; Ibrahim Faisal Halawani; Abdullah A. Alqasem; Reham M. Mashat; et al. (International Dairy Journal, 2026)

Bacteriophage-based vaccination platform for antigen discovery and development of next-generation vaccines - Shahzar Khan; Nadia Ilyas; Aneela Nawaz; Muhammad Ismail Khan; Momina Aamir; Nauman Ahmed Khalid; Aamer Ali Shah; Numan Saleh Zada; Ghulam Shabbir; Malik Badshah; Samiullah Khan (Next Research, 2025)

Leveraging green roof technology: Stakeholder analysis of sustainable urban landscape in the developing regions of South Asia - Mehak Shehzad; Adnan Younis; Sabir Aziz; Muhammad Khizar; Noor ul Ain; Muhammad Asad Shabbir (Land Use Policy, 2025)

Transformation of wet chemically derived ZnGa-LDH to ZnO:GaN nano-alloys for PMS activated wastewater remediation - Yasir Abbas; Kanwal Shabbir; Haider Aziz; Ijaz Hussain; Hafiz M. Adeel Sharif; Muhammad Ahsan Iqbal; Majid Basharat; Haoliang Wang; Niaz Ali Khan (Journal of Environmental Chemical Engineering, 2025)

Climate smart agriculture: A path to sustainable farming in China - Duong Thuy Linh; Muhammad Nadir Shabbir (Food and Humanity, 2025)

Association of PD-1 immune checkpoint polymorphisms with oral cancer risk: results from a Pakistani case-control study - Iqra Mubeen; Arifa Shabbir; Ezzat M. Awad; Humaira Naeemi; Talin Barisani-Asenbauer; Muhammad Usman Rashid; Naila Malkani (Molecular Biology Reports, 2025)

Green Synthesis of Mangifera Indica Mediated NiO and NiMn2O4 Nanomaterials for Electrocatalytic Water Splitting - Fatima Masood; Shabbir Hussain; Muhammad Arif; Shahzad Murtaza; Muhammad Imran; Muhammad Bilal Tahir; Khurram Shahzad Munawar; Hamad M. Alkahtani; Amer Alhaj Zen; Syed Adnan Ali Shah (International Journal of Environmental Research, 2025)

Molecular detection and prevalence of colistin-resistant Escherichia coli in poultry and humans: a one health perspective - Muhammad Najam Ul Huda; Muhammad Zubair Shabbir; Adnan Hasan Tahir; Awais Ali Ahmad; Umar Bin Zahoor; Waqas Ahmad; Ali Raza; Farhan Afzal; Abdur Rauf Khalid; Muhammad Abu Bakr Shabbir (Brazilian Journal of Microbiology, 2025)

Comparative study of extraction methods and process parameters of polyphenolic content obtained from Celosia argentea L. Flower for herbal sunscreen - Humaira Arshad; Adnan Afzal; Arifa Mehreen; Faiza Shakoor; Valisher Sapayev Odilbek Uglu; Saima Qadeer; Samiyah Tasleem; Rana Muhammad Kamran Shabbir; Mukhayya Djumaniyazova (Natural Product Research, 2025)

Exploring the relationships of trade globalization and financial inclusion with energy intensity in emerging economies: The role of technological innovation - Syed Anees Haider Zaidi; Shabbir Ahmad; Muhammad Wasif Zafar; Zokir Mamadiyarov (Journal of Environmental Management, 2025)

Recent advances in beta-type hexagonal ferrites: Synthesis, structural, vibrational and electromagnetic characteristics - M. Irfan; Shafaq Waqar; Hafiz Ghulam Shabbir; Tehreem Idrees; Fatima Khan; Komel Maryam; Maryam Choudhary; Isbah Shamshad; Abdul Rehman Ashiq; Shagufta Gulbadan; Muhammad Azhar Khan; Nayyab Sajjad (Next Research, 2025)

Advancing fungal phylogenetics: integrating modern sequencing, dark taxa discovery, and machine learning - Syed Atif Hasan Naqvi; Aqleem Abbas; Ammarah Hasnain; Zeshan Bilal; Fahad Hakim; Muhammad Shabbir; Ahsan Amin; Muhammad Umer Iqbal (Archives of Microbiology, 2025)

Enhanced electrochemical performance of MoP2-based supercapacitor electrodes through doping with transition, post-transition, and rare earth metals - Mudassar Maraj; Mir Rehman Shabbir; Faisal Ali; Muhammad Hamza Naseer; Ali Haider Bhalli; Sarmad Ali; Nian Li; Xiuhong Li; Zhenyang Wang (Fuel, 2025)

Genotypic Profiling, Functional Analysis, Cholesterol-Lowering Ability, and Angiotensin I-Converting Enzyme (ACE) Inhibitory Activity of Probiotic Lactiplantibacillus plantarum K25 via Different Approaches - Tariq Aziz; Hu Hangyu; Muhammad Naveed; Muhammad Aqib Shabbir; Abid Sarwar; Jasra Nasbeeb; Yang Zhennai; Metab Alharbi (Probiotics and Antimicrobial Proteins, 2025)

Revealing Lactiplantibacillus Plantarum K25 Derived (Z)-18-Octadec-9-Enolide in Modulating Aquaporin-8 in Colorectal Cancer by Bridging the Gut Microbiome and Membrane Biology - Tariq Aziz; Muhammad Aqib Shabbir; Abid Sarwar; Zhennai Yang; Lin Lin; Wafa Abdullah I. Al-Megrin; Ashwag Shami; Maher S. Alwethaynani; Areej A Alhhazmi; Fahad Al-Asmari; Fakhria A. Al-Joufi; Deema Fallatah (Cell Biochemistry and Biophysics, 2025)

Molecular characterization and epidemiological insights into serotypes of foot-and-mouth disease virus in Pakistan - Syeda Anam Masood Gardezi; Masood Rabbani; Muhammad Hassan Mushtaq; Muhammad Zubair Shabbir (Archives of Virology, 2025)

N-Dimethyl chalcone facilitated augmentation of IL-10 and diminution of TNF-α, IL-1β, IL-6, NFκB, and COX-2 in FCA-induced arthritic rat model - Faiza Waseem; Ali Sharif; Maryam Shabbir; Bushra Akhtar; Syed Wadood Ali Shah; Shahnaz; Adeel Arshad; Ejaz Basheer; Muhammad Asif Hanif; Muhammad Ali (Inflammopharmacology, 2025)

Assessing the impact of economic volatility on renewable energy tokens, GCC stock indices, and green assets - Michael Yao-Ping Peng; Boghean Florin; Boghean Carmen; Faur Flaviu Casian; Florin Radu; Violeta Hazaparu; Raul Adrian Lile; Sagheer Muhammad; Malik Shahzad Shabbir (Environment, Development and Sustainability, 2025)

Systematic Computational Designing of Efficient Phenalene and Pyrene Based Derivatives to Tune the Optical and Nonlinear Optical Response - Tazeem Fatima; Shamsa Bibi; Shabbir Muhammad; Shaukat Ali; Muhammad Yaseen (Journal of Fluorescence, 2025)

Investigation of diabetes mellitus transmission in humans by using time delay tool and numerical treatment approach - Ali Raza; Ayesha Shabbir; Umar Shafique; Nauman Ahmed; Muhammad Rafiq (Modeling Earth Systems and Environment, 2025)

In-vitro and in-vivo assessments of greenly synthesized iron oxide nanoparticles from Cascabela thevetia plant extract for the treatment of ventricular septal defect - Amina Abid; Muhammad Naveed; Tariq Aziz; Muhammad Aqib Shabbir; Hira Mubeen; Ayaz Ali Khan; Abdullah F Alsmari (South African Journal of Botany, 2025)

Asymmetric role of board diversity on green growth mechanism: Evidence from COP27 framework - Kamran Mohy-ud-Din; Muhammad Shahbaz; Shoh-Jakhon Khamdamov; Shabbir Ahmad (Journal of Environmental Management, 2025)

Chemically modified filter paper with Jaman fruit extract for visual sensing of milk freshness - Muhammad Naeem Shabbir; Adeel Ahmad; Muhammad Aslam; Ayaz Hassan; Hidayat Ullah; Muhammad Akram; Hafiza Fatima Qayum; Fatima Naeem (Food Chemistry, 2025)

Chemistry, biosynthesis, and theranostics of antioxidant flavonoids and polyphenolics of genus Rhododendron: an overview - Amjad Hussain; Sajjad Azam; Rabia Maqsood; Riaz Anwar; Muhammad Sajid Hamid Akash; Hidayat Hussain; Daijie Wang; Muhammad Imran; Katarzyna Kotwica-Mojzych; Shoaib Khan; Shabbir Hussain; Muhammad Adnan Ayub (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Genetic Divergence Among Sorghum (Sorghum bicolor L.) Genotypes Grown Under Rainfed Conditions - Rafiq Ahmad; Ghulam Shabbir; Syed Farman Ullah; Danish Ibrar; Muhammad Ilyas; Esam M. Al-Shaebi; Yawen Zeng; Abdul Qayyum (Journal of Crop Health, 2025)

Retraction Note: Assessment of Titanium Dioxide Nanoparticles (TiO2-NPs) Induced Hepatotoxicity andAmeliorative Effects of Cinnamomum cassia in Sprague–Dawley Rats - Muhammad Shakeel; Farhat Jabeen; Rehana Iqbal; Abdul Shakoor Chaudhry; Sadia Zafar; Muhammad Ali; Muhammad Saleem Khan; Adeel Khalid; Samina Shabbir; Muhammad Saleem Asghar (Biological Trace Element Research, 2025)

Fungicide resistance in Fusarium species: exploring environmental impacts and sustainable management strategies - Syed Atif Hasan Naqvi; Muhammad Farhan; Muhammad Ahmad; Rafia Kiran; Muhammad Shahbaz; Aqleem Abbas; Fahad Hakim; Muhammad Shabbir; Yee Shin Tan; Jaya Seelan Sathiya Seelan (Archives of Microbiology, 2025)

Applicability of Ni@ZnO polymer nanocomposite as an adsorbent for removal of methylene blue dye from synthetic wastewater: Batch studies and multilinear regression (MLR) modeling - Nazish Jabeen; Tanzeela Gulab Shahzady; Ayesha Mohyuddin; Muhammad Amjad; Fatima Batool; Wajad Ulfat; Shabbir Hussain; Hui Hwang Goh; Tonni Agustiono Kurniawan (Environmental Monitoring and Assessment, 2025)

Interactive effects of melatonin and salicylic acid on Brassica napus under drought condition - Noman Rafique; Noshin Ilyas; Muhammad Aqeel; Naveed Iqbal Raja; Ghulam Shabbir; Muhammad Ajaib; R. Z. Sayyed; Sulaiman Ali Alharbi; Mohammad Javed Ansari (Plant and Soil, 2024)

Association between the variations in metabolic pathways and oral cancer risk: results from a Pakistani case-control study - Arifa Shabbir; Muhammad Usman Rashid; Ezzat M. Awad; Humaira Naeemi; Talin Barisani-Asenbauer; Naila Malkani (Molecular Biology Reports, 2024)

Comparative genomics and evolutionary analysis of dengue virus strains circulating in Pakistan - Aziz Ul-Rahman; Muhammad Zubair Shabbir; Majeeda Rasheed; Nusrat Shafi; Kalsoom AbdulRazaq; Hamna Ramzan; Rauf Mehmood; Junaid Ali Khan (Virus Genes, 2024)

Comprehensive assessment of heavy metal contamination in soil-plant systems and health risks from wastewater-irrigated vegetables - Muhammad Anis Aslam; Muhammad Sohail Abbas; Muhammad Mustaqeem; Maryam Bashir; Adeeba Shabbir; Muhammad Talha Saeed; Rana Muhammad Irfan (Colloids and Surfaces C: Environmental Aspects, 2024)

The expanding host range of lumpy skin disease virus in wild and domestic animals - Aziz Ul-Rahman; Muhammad Zubair Shabbir; Muhammad Asif Raza; Paul Rossiter (Tropical Animal Health and Production, 2024)

Sustainable management in natural resources and carbon neutrality: Revisiting the nexus in Ukraine-Russia war context - Muhammad Shahzad Mubarik; Muhammad Kashif; Mubarra Shabbir; Qasim Jalil (Resources Policy, 2024)

Balancing growth and sustainability: COP 28 policy implications of green energy, industrialization, foreign direct investment, and globalization in South Asia - Muhammad Asif; Nabila Amin; Muhammad Salman Shabbir; Huaming Song (Journal of Environmental Management, 2024)

Effect of naringenin on post-thaw quality, fertility-associated gene expression and fertilization potential of buffalo (Bubalus bubalis) bull sperm - Ghulam Shabbir Khan; Muhammad Zahid Tahir; Muhammad Yasir Zahoor; Hifz-ul-Rahman; Amjad Riaz (Cryobiology, 2024)

Phytochemical profile, nutritional and medicinal value of Nigella sativa - Shabbir Hussain; Aqsa Rukhsar; Munawar Iqbal; Qurat ul Ain; Jahanzaib Fiaz; Noman Akhtar; Maria Afzal; Naveed Ahmad; Iqbal Ahmad; Wissem Mnif; Muhammad Hashir Khalid (Biocatalysis and Agricultural Biotechnology, 2024)

Unraveling the role of natural functional oils in modulating osteoarthritis related complications - Muhammad Asim Shabbir; Fakiha Mehak; Moazzam Rafiq Khan; Waqar Ahmed; Muhammad Furqan Nawaz; Abdo Hassoun; Zuhaib F. Bhat; Rana Muhammad Aadil (Critical Reviews in Food Science and Nutrition, 2024)

Retraction Note: Novel mannich-based derivative of 2-mercaptobenzimidazole (AK7): a new candidate for the treatment of inflammatory arthritis owing to its NF-κB1 inhibitory potential - Gagun Kamran; Hafiz Amir Ali Kharl; Muhammad Nasir Hayat Malik; Waqas Younis; Humaira Nadeem; Aymun Madni Zubair; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Ramla Shabbir; Asma Akram; Irfan Anjum; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Synthesis, Characterization, Photocatalytic and Antimicrobial Potential of Pr2O3/ZnO/gC3N4 Nanocomposite - Kiran Sabir Ali; Kausar Hussain Shah; Hafiz Muhammad Asif; Muhammad Ali Khan; Shabbir Hussain; Muhammad Tariq (International Journal of Environmental Research, 2024)

Retraction Note: Arsenic in drinking water: overview of removal strategies and role of chitosan biosorbent for its remediation - Asif Ayub; Khaysy Srithilat; Irum Fatima; Nadia Masaya Panduro-Tenazoa; Iqbal Ahmed; Muhammad Usman Akhtar; Waqas Shabbir; Khalil Ahmad; Ali Muhammad (Environmental Science and Pollution Research, 2024)

Enhancement in performance of RC beam-column joint under cyclic loading by using various grades of engineered cementitious composites in the joint zone-a sustainable numerical study - Atta Muhammad; Umbreen Us Sahar; Ubaid Ahmad Mughal; Iffat Siddique; Aqsa Shabbir (European Journal of Environmental and Civil Engineering, 2024)

From black to green: Quantifying the impact of economic growth, resource management, and green technologies on CO2 emissions - Muhammad Shahbaz; Nikunj Patel; Anna Min Du; Shabbir Ahmad (Journal of Environmental Management, 2024)

Activation of persulfate, peroxymonosulfate, and peroxydisulfate using metal-organic framework catalysts for degradation of antibiotics: Identification, quantification, interconversion, and transformation of reactive species - Irfan Ijaz; Aysha Bukhari; Attia Shaheen; Ammara Nazir; Ezaz Gilani; Hina Zain; Shabbir Muhammad; Sajjad Hussain (Journal of Environmental Chemical Engineering, 2024)

Unveiling the chemical profile, synergistic antibacterial and hemolytic effects of Cymbopogon citratus and Tachyspermum ammi leaves - Shabbir Hussain; Amina Zahid; Muhammad Imran; Shazma Massey; Muhammad Riaz; Muhammad Sagir; Muhammad Shahid; Wissem Mnif; Shahid Iqbal; Munawar Iqbal; Arif Nazir (Biocatalysis and Agricultural Biotechnology, 2024)

Cadmium induced defense enhance the invasive potential of Wedelia trilobata under herbivore infestation - Mohsin Nawaz; Jianfan Sun; Yanwen Bo; Feng He; Samina Shabbir; Muhammad Umair Hassan; Linxuan Pan; Parvaiz Ahmad; Christian Sonne; Daolin Du (Journal of Hazardous Materials, 2024)

Does green tax theory affect the environmental sustainability and protection? - Muhammad Naveed Ahmad; Xiaoguang Zhou; Sagheer Muhammad; Malik Shahzad Shabbir (Environment, Development and Sustainability, 2024)

Silicon-nanoparticles loaded biochar for soil arsenic immobilization and alleviation of phytotoxicity in barley: Implications for human health risk - Muhammad Asif Naeem; Abrar Shabbir; Muhammad Imran; Sajjad Ahmad; Muhammad Shahid; Behzad Murtaza; Muhammad Amjad; Waqas-ud-Din Khan (Environmental Science and Pollution Research, 2024)

Remediation of organic pollutant from the aqueous environment using in-house fabricated polyaniline-based hybrid composite (PANI-MnPBA/NiCoMnS) materials - Naseem Ahmad Khan; Muhammad Imran; Muhammad Nadeem Akhtar; Shabbir Hussain; Muhammad Azhar Khan; Ashwag Shami; Hafiz Iqbal (Chemosphere, 2024)

Marine Streptomyces sp. PGC 39: A treasure trove of new antimicrobial agents, macrolidycin, and pyrachlomycin - Rabbia Ahmad; Muhammad Imran Tousif; Mamona Nazir; Asma Yaqoob; Syed Adnan Ali Shah; Gokhan Zengin; Abdullahi Ibrahim Uba; Shabbir Muhammad (Food Bioscience, 2024)

Unraveling the impact of eco-centric leadership and pro-environment behaviors in healthcare organizations: Role of green consciousness - Ali Hasan; Xiang Zhang; Di Mao; Muhammad Kashif; Farhan Mirza; Rabia Shabbir (Journal of Cleaner Production, 2024)

Nutraceutical and Health-Promoting Potential of Lactoferrin, an Iron-Binding Protein in Human and Animal: Current Knowledge - Muhammad Faizan Ashraf; Dawood Zubair; Muhammad Noaman Bashir; Mahmoud Alagawany; Shabbir Ahmed; Qurban Ali Shah; Jameel Ahmed Buzdar; Muhammad Asif Arain (Biological Trace Element Research, 2024)

Performance comparison of a photosynthetic and mechanically aerated microbial fuel cell for wastewater treatment and bioenergy generation using different anolytes - Zia Ullah; Zeshan Sheikh; Waqas Qamar Zaman; Muhammad Zeeshan; Waheed Miran; Jiansheng Li; Muhammad Abdul Nasir Khan; Sahar Saleem; Shanza Shabbir (Journal of Water Process Engineering, 2023)

Proteosomes based on milk phospholipids and proteins to enhance the stability and bioaccessibility of β-carotene - Bina Zarif; Saima Shabbir; Ramla Shahid; Tayyaba Noor; Muhammad Imran (Food Chemistry, 2023)

Unlocking the secrets of soil microbes: How decades-long contamination and heavy metals accumulation from sewage water and industrial effluents shape soil biological health - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Niaz Ahmed; Sajjad Hussain; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Javeed Shabbir Dar; Mahmoud Moustafa; Mohammed O. Alshaharni (Chemosphere, 2023)

Glutathione and zinc application upregulate the antioxidant system increasing photosynthetic pigments and growth under water stress in maize (Zea mays L.) - Farah Saeed; Abida Kausar; Qasim Ali; Athar Mahmood; Talha Javed; Rubab Shabbir; Muhammad Fraz Ali (Brazilian Journal of Botany, 2023)

Simultaneous removal of Norfloxacin, Ciprofloxacin, and copper from aqueous solution by chitosan and MXene functionalized graphene oxide ternary composite based on anion-synergistic interaction - Aysha Bukhari; Irfan Ijaz; Ezaz Gilani; Ammara Nazir; Hina Zain; Shabbir Muhammad; Awais Bukhari; Attia shaheen; Sajjad Hussain (Chemical Engineering Journal, 2023)

Comparative immunocompetence and interspecies transmission of avian orthoavulavirus-1 in feral birds originating from rural and urban settings - Momena Habib; Aziz Ul-Rahman; Zia-ur-Rehman; Muhammad Akbar Shahid; Noreen Sarwar; Muhammad Bilal; Muhammad Saeed Imran; Muhammad Munir; Shaista Abbas; Muhammad Zubair Shabbir (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Milk phospholipids and buttermilk based composite nanosystems for enhanced stability and bioaccessibility of β-carotene - Bina Zarif; Saima Shabbir; Abdur Rahman; Tauqir A. Sherazi; Ramla Shahid; Tayyaba Noor; Muhammad Imran (International Dairy Journal, 2023)

Use of agricultural bio-wastes to remove arsenic from contaminated water - Zunaira Shabbir; Muhammad Shahid; Natasha; Sana Khalid; Samina Khalid; Muhammad Imran; Muhammad Imran Qureshi; Nabeel Khan Niazi (Environmental Geochemistry and Health, 2023)

A critical analysis of wastewater use in agriculture and associated health risks in Pakistan - Natasha; Muhammad Shahid; Sana Khalid; Behzad Murtaza; Hasnain Anwar; Ali Haidar Shah; Aneeza Sardar; Zunaira Shabbir; Nabeel Khan Niazi (Environmental Geochemistry and Health, 2023)

Does clean energy matter? The dynamic effects of different strategies of renewable energy, carbon emissions, and trade openness on sustainable economic growth - Jianrun Wang; Muhammad Ramzan; Fauzia Makin; Ch Kamran Mahmood; Carlos Samuel Ramos-Meza; Vipin Jain; Malik Shahzad Shabbir (Environment, Development and Sustainability, 2023)

Radiological risk assessment from the Gamma spectrometry of soil samples in the vicinity of a research centre in Nilore, Pakistan - Tahira Shabbir; Muhammad Sohail; Rizwan Ahmed; Masroor Ahmad; Khizar Hayat Satti (Environmental Monitoring and Assessment, 2023)

Temporal study of wastewater surveillance from September 2020 to March 2021: an estimation of COVID-19 patients in Lahore, Pakistan - Muhammad Adnan Ashraf; Muhammad Nawaz; Ali Asif; Muhammad Asad Ali; Adnan Mehmood; Muhammad Waqar Aziz; Muhammad Zubair Shabbir; Nadia Mukhtar; Muhammad Abu Bakr Shabbir; Sohail Raza; Tahir Yaqub (Environmental Science and Pollution Research, 2023)

Development of Mn-MOF/CuO composites as platform for efficient electrocatalytic OER - Bushra Shabbir; Nidhal Drissi; Karam Jabbour; Abdelaziz Gassoumi; F.F. Alharbi; Sumaira Manzoor; Muhammad Faheem Ashiq; H.A. Alburaih; Muhammad Fahad Ehsan; Muhammad Naeem Ashiq (Fuel, 2023)

Potential of pectin-chitosan based composite films embedded with quercetin-loaded nanofillers to control meat associated spoilage bacteria - Syed Muhammad Afroz Ali; Taskeen Niaz; Anas Munir; Ramla Shahid; Saima Shabbir; Tayyaba Noor; Muhammad Imran (Food Bioscience, 2023)

Assessment of formulation variables of poor water soluble diacerein for its improved loading and anti-inflammatory activity - Maryam Shabbir; Kashif Barkat; Muhammad Umer Ashraf; Uzair Nagra; Syed Nisar Hussain Shah (Drug Delivery and Translational Research, 2023)

RETRACTED ARTICLE: Novel mannich-based derivative of 2-mercaptobenzimidazole (AK7): a new candidate for the treatment of inflammatory arthritis owing to its NF-κB1 inhibitory potential - Gagun Kamran; Hafiz Amir Ali Kharl; Muhammad Nasir Hayat Malik; Waqas Younis; Humaira Nadeem; Aymun Madni Zubair; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Ramla Shabbir; Asma Akram; Irfan Anjum; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Polyelectrolyte multilayers coating of aliphatic polyamide anion-exchange membranes to increase monovalent/divalent anions selectivity in electrodialysis - Muhammad Ahmad; Mahmood Ahmed; Shabbir Hussain; Abid Ali; Manzar Zahra; Muhammad Imran Din; Zeeshan Mustafa (Desalination, 2023)

Impact of economic and green growth on poverty, income inequalities, and environmental degradation: a case of South Asian economies - Shazia Kousar; Aamir Inam Bhutta; Muhammad Rizwan Ullah; Aiza Shabbir (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Does environmental sustainability affect the renewable energy consumption? Nexus among trade openness, CO2 emissions, income inequality, renewable energy, and economic growth in OECD countries - Iftikhar Muhammad; Rasim Ozcan; Vipin Jain; Paritosh Sharma; Malik Shahzad Shabbir (Environmental Science and Pollution Research, 2022)

Synthesis, theoretical investigations and biological evaluation of ibuprofen drug hybrids - Adina Tatheer; Shahzad Murtaza; Naghmana Kausar; Ataf Ali Altaf; Samia Kausar; Safeer Ahmed; Shabbir Muhammad; Amjad Hussain (Medicinal Chemistry Research, 2022)

A time series forecasting analysis of overall and sector-based natural gas demand: a developing South Asian economy case - Anwar Hussain; Junaid Alam Memon; Muntasir Murshed; Md Shabbir Alam; Usman Mehmood; Mohammad Noor Alam; Muhammad Rahman; Umar Hayat (Environmental Science and Pollution Research, 2022)

Eco-friendly acid dyeing of silk and wool fabrics using Acid Violet 49 dye - Muhammad Usama Shabbir; Shahid Adeel; Tanveer Hussain Bokhari; Muhammad Usman; Muhammad Kaleem Khosa; Tanvir Ahmad; Asma Inayat (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Arsenic in drinking water: overview of removal strategies and role of chitosan biosorbent for its remediation - Asif Ayub; Khaysy Srithilat; Irum Fatima; Nadia Masaya Panduro-Tenazoa; Iqbal Ahmed; Muhammad Usman Akhtar; Waqas Shabbir; Khalil Ahmad; Ali Muhammad (Environmental Science and Pollution Research, 2022)

Differential neuroprotective effect of curcuminoid formulations in aluminum chloride–induced Alzheimer’s disease - Anam Shabbir; Kanwal Rehman; Muhammad Sajid Hamid Akash; Moazzama Akbar; Zunera Chaudhary; Pharkphoom Panichayupakaranant; Muhammad Ajmal Shah (Environmental Science and Pollution Research, 2022)

Determination and detoxification of aflatoxin and ochratoxin in maize from different regions of Pakistan - Syed Wajih ul Hassan Shah Gillani; Yumna Sadef; Muhammad Imran; Hafiz Muhammad Fahad Raza; Aamir Ghani; Sumera Anwar; Muhammad Yasin Ashraf; Shabbir Hussain (Environmental Monitoring and Assessment, 2022)

Nexus between non-renewable energy production, CO2 emissions, and healthcare spending in OECD economies - Hummera Saleem; Muhammad Bilal Khan; Malik Shahzad Shabbir; Ghulam Yahya Khan; Muhammad Usman (Environmental Science and Pollution Research, 2022)

Carica papaya ameliorates thrombocytopenia through upregulation of Interleukin-11 and modulation of thrombopoietin in mouse model of carboplatin-induced myelosuppression - Sabeen Irshad; Arham Shabbir; Hina Aslam; Tasleem Akhtar; Muhammad Shahzad (Molecular Biology Reports, 2022)

Nickel tolerance and phytoremediation potential of quinoa are modulated under salinity: multivariate comparison of physiological and biochemical attributes - Naila Naheed; Ghulam Abbas; Muhammad Asif Naeem; Munawar Hussain; Rahat Shabbir; Saud Alamri; Manzer H. Siddiqui; Muhammad Zahid Mumtaz (Environmental Geochemistry and Health, 2022)

The dynamic impact of renewable energy sources on environmental economic growth: evidence from selected Asian economies - Muhammad Khalid Anser; Muhammad Usman; Muhammad Sharif; Sana Bashir; Malik Shahzad Shabbir; Ghulam Yahya Khan; Lydia Bares Lopez (Environmental Science and Pollution Research, 2022)

Salinity modulates lead (Pb) tolerance and phytoremediation potential of quinoa: a multivariate comparison of physiological and biochemical attributes - Azka Iftikhar; Ghulam Abbas; Muhammad Saqib; Arslan Shabbir; Muhammad Amjad; Muhammad Shahid; Iftikhar Ahmad; Shahid Iqbal; Saeed Ahmad Qaisrani (Environmental Geochemistry and Health, 2022)

Correction to: Does globalization affect the green economy and environment? The relationship between energy consumption, carbon dioxide emissions, and economic growth - Muhammad Khalid Anser; Muhammad Usman; Danish Iqbal Godil; Malik Shahzad Shabbir; Arshian Sharif; Mosab Ismail Tabash; Lydia Bares Lopez (Environmental Science and Pollution Research, 2021)

Does globalization affect the green economy and environment? The relationship between energy consumption, carbon dioxide emissions, and economic growth - Muhammad Khalid Anser; Muhammad Usman; Danish Iqbal Godil; Malik Shahzad Shabbir; Arshian Sharif; Mosab I. Tabash; Lydia Bares Lopez (Environmental Science and Pollution Research, 2021)

An in vitro antiviral activity of iodine complexes against SARS-CoV-2 - Imran Altaf; Muhammad Faisal Nadeem; Nadir Hussain; Muhammad Nawaz; Sohail Raza; Muhammad Abu bakr Shabbir; Muhammad Adnan Ashraf; Muhammad Asad Ali; Sohail Hassan; Muhammad Waqar Aziz; Nazish Matti; Muhammad Ashraf; et al. (Archives of Microbiology, 2021)

The glutathione S-transferase (PxGST2L) may contribute to the detoxification metabolism of chlorantraniliprole in Plutella xylostella(L.) - Fei Yin; Qingsheng Lin; Xiaoxiang Wang; Zhenyu Li; Xia Feng; Muhammad Zeeshan Shabbir (Ecotoxicology, 2021)
The diamondback moth ( Plutella xylostella L.), is an economic pest of cruciferous plants worldwide, which causes great economic loss to cruciferous plants production. However, the pest has developed resistance to insecticides. One of such insecticides is chlorantraniliprole. The study of the mechanisms underlying resistance is key for the effective management of resistance. In this study, a comparative proteomics approach was used to isolate and identify various proteins that differed between chlorantraniliprole-susceptible and -resistant strains of P. xylostella . Eleven proteins were significantly different and were successfully identified by MALDI-TOF-MS. Metabolism-related proteins accounted for the highest proportion among the eleven different proteins. The function of the PxGST2L protein was validated by RNAi. Knockdown of PxGST2L reduced the GST activity and increased the toxicity of chlorantraniliprole to the diamondback moth. The resistance ratio of diamondback moth to chlorantraniliprole was reduced from 1029 to 505. The results indicated that PxGST2L is partly responsible for chlorantraniliprole insecticide resistance in DBM. Our finding contributes to the understanding of the mechanism underlying resistance to chlorantraniliprole in the DBM, to develop effective resistance management tactics.

The interplay between the immune system and SARS-CoV-2 in COVID-19 patients - Sana Shabbir; Muhammad Hassan Raza; Muhammad Arshad; Muhammad Jawad Khan (Archives of Virology, 2021)

Elucidating the Photoluminescence Quenching in Ensulizole: an Artificial Water Soluble Sunscreen - Muhammad Mubeen; Muhammad Adnan Khalid; Maria Mukhtar; Saba Shahrum; Shanila Zahra; Saima Shabbir; Azhar Iqbal (Journal of Fluorescence, 2021)

RETRACTED ARTICLE: Closed-loop supply chain network design with sustainability and resiliency criteria - Muhammad Salman Shabbir; Arshad Mahmood; Roy Setiawan; Chairun Nasirin; Rusdiyanto Rusdiyanto; Gazali Gazali; Mohd Anuar Arshad; Shahid Khan; Fatima Batool (Environmental Science and Pollution Research, 2021)

Effects of soil application of two different fipronil formulations on some soil-dwelling non-target arthropods - Muhammad Asad; Sohail Ahmed; Rashad Rasool Khan; Abid Ali; Muhammad Fahad Raza; Ammarah Shabbir; Faisal Munir; Anam Noreen Abbas; Mubashir Tariq (International Journal of Tropical Insect Science, 2021)

Nexus between willingness to pay for renewable energy sources: evidence from Turkey - Iftikhar Muhammad; Malik Shahzad Shabbir; Sharjeel Saleem; Kanwal Bilal; Recep Ulucak (Environmental Science and Pollution Research, 2021)

Frequency of PPAR-γ, FTO and ABCC8 genetic variation in Pakistani cardiovascular smokers - Kanwal Rehman; Ayesha Tahir; Sania Niaz; Sara Shabbir; Komal Jabeen; Amna Faheem; Muhammad Sajid Hamid Akash (Environmental Science and Pollution Research, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

A comparative phylogenomic analysis of SARS-CoV-2 strains reported from non-human mammalian species and environmental samples - Aziz Ul-Rahman; Muhammad Abu Bakr Shabbir; Muhammad Waqar Aziz; Saima Yaqub; Asif Mehmood; Muhammad Asif Raza; Muhammad Zubair Shabbir (Molecular Biology Reports, 2020)

Advances in photo-catalysis approach for the removal of toxic personal care product in aqueous environment - Muhammad Bilal Tahir; Anam Ahmad; Tahir Iqbal; Mohsin Ijaz; Shabbir Muhammad; Saifeldin M. Siddeeg (Environment, Development and Sustainability, 2020)

Cadmium Partitioning, Physiological and Oxidative Stress Responses in Marigold (Calendula calypso) Grown on Contaminated Soil: Implications for Phytoremediation - Amjad Farooq; Muhammad Nadeem; Ghulam Abbas; Arslan Shabbir; Muhammad Shafique Khalid; Hafiz Muhammad Rashad Javeed; Muhammad Farhan Saeed; Ahsan Akram; Adnan Younis; Gulzar Akhtar (Bulletin of Environmental Contamination and Toxicology, 2020)

A comparative evaluation of serum biochemistry profile and antigenic relatedness among velogenic and mesogenic Avian avulavirus 1 infection in chickens and pigeons - Aziz Ul-Rahman; Muhammad Abu Bakr Shabbir; Mushtaq Ahmed; Muhammad Zubair Shabbir (Tropical Animal Health and Production, 2020)

Assessing the climate change impacts and adaptation strategies for rice production in Punjab, Pakistan - Ghulam Shabbir; Tasneem Khaliq; Ashfaq Ahmad; Muhammad Saqib (Environmental Science and Pollution Research, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

The role of financial development, energy demand, and technological change in environmental sustainability agenda: evidence from selected Asian countries - Hummera Saleem; Muhammad Bilal Khan; Malik Shahzad Shabbir (Environmental Science and Pollution Research, 2020)

Assessment of arsenic exposure by drinking well water and associated carcinogenic risk in peri-urban areas of Vehari, Pakistan - Ali Haidar Shah; Muhammad Shahid; Sana Khalid; Natasha; Zunaira Shabbir; Hafiz Faiq Bakhat; Behzad Murtaza; Amjad Farooq; Muhammad Akram; Ghulam Mustafa Shah; Wajid Nasim; Nabeel Khan Niazi (Environmental Geochemistry and Health, 2020)

Circulation of multiple subtypes (A, G and CRFs 02_AG) of human immunodeficiency virus type 1 (HIV-1) in selected districts of Punjab province, Pakistan - Saima Yaqub; Tahir Yaqub; Muhammad Zubair Shabbir; Asif Nadeem; Nadia Mukhtar; Firnas Ata Ur Rehman; Aziz-ul Rahman; Muhammad Furqan Shahid; Muzaffar Ali; Tayyebah Sohail; Zarfishan Tahir (Archives of Virology, 2019)

A comparative phylogenomic analysis of peste des petits ruminants virus isolated from wild and unusual hosts - Aziz-ul- Rahman; Muhammad Munir; Muhammad Zubair Shabbir (Molecular Biology Reports, 2019)

A comparative genomic and evolutionary analysis of circulating strains of Avian avulavirus 1 in Pakistan - Aziz-ul Rahman; Muhammad Munir; Muhammad Zubair Shabbir (Molecular Genetics and Genomics, 2019)

Emergence and genetic analysis of variant pathogenic 4/91 (serotype 793/B) infectious bronchitis virus in Egypt during 2019 - Mohammed A. Rohaim; Rania F. El Naggar; Mohamed M. Hamoud; Abdel-Hamid I. Bazid; Abdulrhman M. Gamal; Samah E. Laban; Mohammed A. Abdel-Sabour; Shimaa A. E. Nasr; Manal M. Zaki; Muhammad Z. Shabbir; Osama K. Zahran; Muhammad Munir (Virus Genes, 2019)

A comparative phylogenomic analysis of avian avulavirus 1 isolated from non-avian hosts: conquering new frontiers of zoonotic potential among species - Aziz Ul-Rahman; Muhammad Zubair Shabbir (Archives of Virology, 2019)

Peste des petits ruminants in wild ungulates - Aziz-ul-Rahman; Jonas Johansson Wensman; Muhammad Abubakar; Muhammad Zubair Shabbir; Paul Rossiter (Tropical Animal Health and Production, 2018)

Genomic and biological characterization of Newcastle disease viruses isolated from migratory mallards (Anas platyrhynchos) - Momena Habib; Tahir Yaqub; Jawad Nazir; Wasim Shehzad; Aziz-ul-Rahman; Tayyebah Sohail; Nadia Mukhtar; Arsalan Mehboob; Muhammad Munir; Muhammad Zubair Shabbir (Archives of Virology, 2018)

Socio-demographic characters, distribution and transformation of iodine in soil, plant and wheat grains at District Diamer, Gilgit-Baltistan, Pakistan - Faridullah; Didar Ahmad; Hina Shabbir; Toqeer Ahmed; Muhammad Irshad; Arif Alam; Asif Sardar (Environmental Geochemistry and Health, 2018)

RETRACTED ARTICLE: Assessment of Titanium Dioxide Nanoparticles (TiO2-NPs) Induced Hepatotoxicity and Ameliorative Effects of Cinnamomum cassia in Sprague-Dawley Rats - Muhammad Shakeel; Farhat Jabeen; Rehana Iqbal; Abdul Shakoor Chaudhry; Sadia Zafar; Muhammad Ali; Muhammad Saleem Khan; Adeel Khalid; Samina Shabbir; Muhammad Saleem Asghar (Biological Trace Element Research, 2018)

Understanding brassinosteroid-regulated mechanisms to improve stress tolerance in plants: a critical review - Fahim Nawaz; Muhammad Naeem; Bilal Zulfiqar; Asim Akram; Muhammad Yasin Ashraf; Muhammad Raheel; Rana Nauman Shabbir; Rai Altaf Hussain; Irfan Anwar; Muhammad Aurangzaib (Environmental Science and Pollution Research, 2017)

Determination of Serum Trace Elements (Zn, Cu, and Fe) in Pakistani Patients with Rheumatoid Arthritis - Zia Ullah; Muhammad Ikram Ullah; Shabbir Hussain; Haiba Kaul; Khalid P. Lone (Biological Trace Element Research, 2017)

What do we really know about alien plant invasion? A review of the invasion mechanism of one of the world’s worst weeds - Ali Ahsan Bajwa; Bhagirath Singh Chauhan; Muhammad Farooq; Asad Shabbir; Steve William Adkins (Planta, 2016)

Toxicity of Nano-Titanium Dioxide (TiO2-NP) Through Various Routes of Exposure: a Review - Muhammad Shakeel; Farhat Jabeen; Samina Shabbir; Muhammad Saleem Asghar; Muhammad Saleem Khan; Abdul Shakoor Chaudhry (Biological Trace Element Research, 2016)

Molecular characterization of infectious bursal disease viruses from Pakistan - Muhammad Zubair Shabbir; Muhammad Ali; Muhammad Abbas; Umer Naveed Chaudhry; Zia-ur-Rehman; Muhammad Munir (Archives of Virology, 2016)

Amberinone, a new guaianolide from Amberboa ramosa - Muhammad Ibrahim; Iqbal Hussain; Nusrat Hussain; Arruje Hameed; Tahir Farooq; Amjad Hussain; Muhammad Sajid Hamid Akash; Shabbir Hussain (Natural Product Research, 2016)

Effect of Thermal Treatment on Meat Proteins with Special Reference to Heterocyclic Aromatic Amines (HAAs) - Muhammad Asim Shabbir; Ali Raza; Faqir Muhammad Anjum; Moazzam Rafiq Khan; Hafiz Ansar Rasul Suleria (Critical Reviews in Food Science and Nutrition, 2015)

Distinctive microRNA expression signatures in proton-irradiated mice - Shahid Yar Khan; Muhammad Akram Tariq; James Patrick Perrott; Christopher Drew Brumbaugh; Hyunsung John Kim; Muhammad Imran Shabbir; Govindarajan T. Ramesh; Nader Pourmand (Molecular and Cellular Biochemistry, 2013)

Genetic analysis of Newcastle disease virus from Punjab, Pakistan - Muhammad Zubair Shabbir; Muhammad Abbas; Tahir Yaqub; Nadia Mukhtar; Atta Subhani; Hasham Habib; Muhammad Umar Sohail; Muhammad Munir (Virus Genes, 2013)

Autosomal recessive nonsyndromic deafness locus DFNB63 at chromosome 11q13.2–q13.3 - Shahid Y. Khan; Saima Riazuddin; Muhammad Tariq; Saima Anwar; Muhammad I. Shabbir; S. Amer Riazuddin; Shaheen N. Khan; Tayyab Husnain; Zubair M. Ahmed; Thomas B. Friedman; Sheikh Riazuddin (Human Genetics, 2007)